2010
DOI: 10.1074/jbc.m109.093039
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Inhibits Transforming Growth Factor β Signaling by Promoting Smad2/3 Degradation

Abstract: Estrogen is a growth factor that stimulates cell proliferation. The effects of estrogen are mediated through the estrogen receptors, ER␣ and ER␤, which function as ligand-induced transcription factors and belong to the nuclear receptor superfamily. On the other hand, TGF-␤ acts as a cell growth inhibitor, and its signaling is transduced by Smads. Although a number of studies have been made on the cross-talk between estrogen/ER␣ and TGF-␤/Smad signaling, whose molecular mechanisms remain to be determined. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
114
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 42 publications
5
114
1
1
Order By: Relevance
“…Estrogen treatment is shown to reduce the phosphorylation of Smad2 and Smad3 [231]. when ERα is in a ligand activated form, it physically interacts with Smad2 and Smad3 [231].…”
Section: Crosstalk With Tgf-β Signalingmentioning
confidence: 99%
See 4 more Smart Citations
“…Estrogen treatment is shown to reduce the phosphorylation of Smad2 and Smad3 [231]. when ERα is in a ligand activated form, it physically interacts with Smad2 and Smad3 [231].…”
Section: Crosstalk With Tgf-β Signalingmentioning
confidence: 99%
“…Estrogen receptor activation is shown to inhibit transcriptional activity of TGF-β as determined by reporter assays by up to 60 % [231]. Furthermore, microarray analysis of MCF-7 breast cancer cells revealed that TGF-β treatment more than doubles the expression of 956 genes whereas estrogen treatment reduces the expression of 683 genes [231]. ERα is a major modifier of TGF-β signaling cascade, and activin and ER signaling suppress one another [232].…”
Section: Crosstalk With Tgf-β Signalingmentioning
confidence: 99%
See 3 more Smart Citations